Persepsi Pemilih Pemula Terhadap Penggunaan Media Sosial Sebagai Sarana Kampaye Pada Pemilu 2024 - Wa Ode Mudiani (Departement of Mathematics Education, 2023)
Currently, students cannot be separated from the use of social media in everyday life, both for personal matters and to seek political preferences. Today's youth use of social media to participate in politics is more open. This study aims to determine the perceptions of first-time voters regarding the use of social media as a campaign tool in the 2024 election. The respondents used in this study were 2nd and 3rd grade students at SMA Negeri 4 Wangi-Wangi Selatan, Wakatobi Regency, Southeast Sulawesi, who were taken randomly as many as 30 people. Primary data sources for this research are quantitative and qualitative data analysis methods. Quantitative research uses a questionnaire, while qualitative research uses a descriptive approach through interviews. The percentage of first-time voters who choose to use social media as a campaign tool in the 2024 election by political candidates shows that 76.7% strongly agree, and as many as 60% of respondents vote effectively. Beginner voters recommend several types of social media, such as Facebook, followed by Instagram, Twitter, WhatsApp, and the lowestis YouTube.